Deriving Priorities: Analytical Hierarchy Process (AHP) Approach (Case Study Of Traditional Gedogan Weaving Craft Products, Ranggo Village, Dompu, West Nusa Tenggara) - Kesuma, Agus; Amalia, Siti (Technium Social Sciences Journal, 2024)
The objective of this study is to use the Analytical Hierarchy Process (AHP) method to prioritize alternative marketing strategies for traditional weaving handicrafts in Ranggo Village, Dompu, West Nusa Tenggara. The data for this study came from the questionnaire that traditional weaving craft business owners received. AHP ranks five criteria according to their weight: product, price, promotion, market segmentation, and market position. The study’s findings show that the product has the most weight (1.98), followed by the price (1.49), market segmentation (0.99), promotion (0.71), and market position (0.41). In general, the research indicates that the marketing strategy of Gedogan’s traditional weaving craft products is characterized by the following priority orders and critical components: product quality, price, market segmentation, promotion, and market position.